Discovering Diverse Roles of Peroxidases and Catalases in Photosynthetic and Non-Photosynthetic Eukaryotes - Marcel Zámocký (MDPI AG, 2022)
This Special Issue of Antioxidants, dedicated to "The Role of Peroxidases and Catalases in Photosynthetic and Non-photosynthetic Eukaryotes", was accomplished with the contribution of five original research articles and two detailed reviews [...]